SOSIALISASI PUSAT INFORMASI DAN KONSELING REMAJA DALAM KEGIATAN PEMBERDAYAAN MASYARAKAT DI KAMPUNG KB CAHAYA KENCANA KELURAHAN SIDODAMAI TAHUN 2019 - habybah, lukluk - (Jurnal Pengabdian Masyarakat Fakultas Teknik : Jurnal Abditek, 2022)
The problems found in the KB Cahaya Kencana Village are KB Kader Kampung Cahaya Kencana many but only a few are active, lack of support from stakeholders, there are problems with RT around the KB Cahaya Kencana Village, facilities and infrastructure are still not optimal, funding for village development KB Cahaya Kencana is still lacking, lack of educational media for the Cahaya Kencana KB village. The lack of a PIK-R in the Cahaya Kencana KB village is difficult to meet with the PLKB chairman. The purpose of this study was to increase awareness of the importance of preparing a good future through the socialization of KB and PIK-R villages to residents and health cadres who resided in the KB Cahaya Kencana Village, Sidodamai Village. The method used in community empowerment is community recognition, problem recognition, planning awareness models, implementation, evaluation and monitoring. Methods of data collection in the form of observation data and interview data to the KB Village. Based on the results of community empowerment, KB Cahaya Kencana Village went well, the community was enthusiastic and enthusiasm to participate in the socialization and was trying their best for the KB Cahaya Kencana village so they could launch and run well and smoothly. Keywords: problems KB Village